The Establishment of a Permanent Fire Brigade in Peterhof - Andrey A. Efimov (Вестник Северного (Арктического) федерального университета: Серия «Гуманитарные и социальные науки»)
This article covers the history of the establishment of such an important organization for any town as a fire service. The author notes that it was initiated by the head of the local palace administration Ya.Ya. Eichen, who on March 9, 1837 wrote a letter to the chief manager of palace administrations Ya.V. Zakharzhevsky regarding this issue. The request to approve the establishment of a fire brigade was motivated by the expanding urban development, since many buildings were made of wood and could be significantly damaged by fire. It was suggested to use the fire brigade of one of the Tsarskoye Selo police units as a model. The article highlights that the implementation of this project required substantial bureaucratic work since it involved coordinating the organizational structure of the new unit and ensuring its logistic support. For information and clarifications Peterhof officials turned to Tsarskoye Selo, which was taken as the primary reference point, as well as to Oranienbaum, the nearest district town that had its own fire brigade at the time, and even to the capital, Saint Petersburg. In addition, an important problem was the accommodation of the fire brigade, which was solved both through the optimization of the available areas and by developing a project for the construction of a new building. The author points out that the process of approval and formal organization took around 4 years and ended in late 1841. However, the actual work of the fire brigade did not begin until 1842. The desire to both economize and properly equip the brigade according to the regulations that were in force at that time was the reason behind the lengthy implementation of the idea of creating a fire service in Peterhof.